2018
DOI: 10.1002/chem.201801121
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Vibrational Spectroscopy of α‐Aminoisobutyric Acid Foldamers in Organic Solvents and Phospholipid Bilayers

Abstract: Helical α-aminoisobutyric acid (Aib) foldamers show great potential as devices for the communication of conformational information across phospholipid bilayers, but determining their conformation in bilayers remains a challenge. In the present study, Raman, Raman optical activity (ROA), infrared (IR) and vibrational circular dichroism (VCD) spectroscopies have been used to analyze the conformational preferences of Aib foldamers in solution and when interacting with bilayers. A 3 -helix marker band at 1665-1668… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(65 citation statements)
references
References 81 publications
1
64
0
Order By: Relevance
“…This change is ascribed to perturbation of the response from the reporter rather than a change in the screw-sense of the foldamer. 27 The sensitivity ratio for foldamers 29 , 30 , 35–38 in bilayers was therefore below 1. Inversion of the S R value for ( S , S -BisPyrEt)NHAc-terminated foldamers 37 and 38 in bilayers (1/ S R = 1.3) allows meaningful comparison to the S R values for 37 and 38 in organic solution ( S R = 2.7) and reveals a reduced sensitivity to conformational change when in bilayers.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This change is ascribed to perturbation of the response from the reporter rather than a change in the screw-sense of the foldamer. 27 The sensitivity ratio for foldamers 29 , 30 , 35–38 in bilayers was therefore below 1. Inversion of the S R value for ( S , S -BisPyrEt)NHAc-terminated foldamers 37 and 38 in bilayers (1/ S R = 1.3) allows meaningful comparison to the S R values for 37 and 38 in organic solution ( S R = 2.7) and reveals a reduced sensitivity to conformational change when in bilayers.…”
Section: Resultsmentioning
confidence: 94%
“… 35 Recent vibrational circular dichroism studies of enantiomeric Aib foldamers embedded in phospholipid bilayers hinted that phospholipid chirality may produce diastereoisomeric conformations. 27 Therefore the availability of two pairs of enantiomeric foldamers bearing bis(pyrene) reporters ( 38 and 49 ; 43 and 47 ) offers a unique opportunity to observe chiral induction due to the phospholipids that constitute the bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…Raman and ROA : Previous ROA and VCD studies of peptides ( S )‐ 1 and ( R )‐ 1 have shown that these peptides adopt a partial 3 10 helix conformation in organic solvents like DMSO [8] . Figure 4 shows the Raman and ROA spectra of ( S )‐ 1 and ( R )‐ 1 embedded in vesicles.…”
Section: Resultsmentioning
confidence: 97%
“…A related class of peptide, comprising short synthetic Aib‐rich foldamers, also display membrane activity and have been employed to mimic membrane‐active molecules, including peptaibols [6,7] . The high content of Aib residues in these foldamers leads to the adoption of both P (right‐handed) and M (left‐handed) 3 10 helical conformations, and their high hydrophobicity is similar to that of the naturally occurring peptaibols [5,8–10] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation